Renal protective effects of vicenin-2 and scolymoside in a mouse model of sepsis - Bong-Seon Lee; Sumin Yang; Changhun Lee; Sae-Kwang Ku; Jong-Sup Bae (Universidade de São Paulo, 2020)
This study was initiated to determine whether 2 structurally related flavonoids found in Cyclopia subternata-vicenin-2 (VCN) and scolymoside (SCL)-could modulate renal functional damage in a mouse model of sepsis, and to elucidate the relevant underlying mechanisms. The potential of VCN and SCL treatment to reduce renal damage induced by cecal ligation and puncture (CLP) surgery in mice was measured via assessment of serum creatinine, blood urea nitrogen (BUN), lipid peroxidation, total glutathione, glutathione peroxidase activity, catalase activity, and superoxide dismutase activity. Treatment with either VCN or SCL resulted in elevated plasma levels of BUN and creatinine, and of protein in the urine of mice with CLP-induced renal damage. Moreover, both VCN and SCL inhibited nuclear factor κB activation and reduced the induction of nitric oxide synthase and excessive production of nitric acid. VCN and SCL treatment also reduced the plasma levels of interleukin-6, and tumor necrosis factor-α, reduced lethality due to CLP-induced sepsis, increased lipid peroxidation, and markedly enhanced the antioxidant defense system by restoring the levels of superoxide dismutase, glutathione peroxidase, and catalase in kidney tissues. The present results suggest that VCN and SCL protect mice from sepsis-triggered renal injury.